SURGICAL SITE INFECTIONS, AN EXPERIENCE AT TERTIARY CARE HOSPITAL - Lailama Shah; Shahzada Amir Muhammad Baber; Shabir Ahmed Lehri; Muhammad iqbal Khan; Ibrahim Baloch; Riffat Arbab (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Surgical site (SSI) infections are important cause of morbidity and mortality in admitted patients worldwide. The objective is to determine the incidence of surgical site infection in General Surgical ward of tertiary care hospital.METHODOLOGY: Analytical cross-sectional study conducted at Department of General Surgery, Bolan Medical College/ Post-Graduate Medical Institute Quetta (PGMI) for a period of one year from 1st August 2019 to 31st July 2020.  Descriptive statistics were used to present social economics, factors related to surgery and surgical antimicrobial prophylaxis received. Chi square test was used for checking association between infections and different factors keeping p≤ 0.05 as significant.RESULTS: A total of 1500 patients underwent surgery, of which 500 (33.33%) patients were operated as elective cases and 1000 (66.66%) cases as emergency. Out of total 600 (40%) patients developed Surgical Site Infection (SSI). Risk associated with higher incidence of SSI was found to be age (30-45 years) and Diabetes mellitus (uncontrolled diabetes in perioperative period). Postoperatively obesity was noted to be having significant effect with p=0.002, American Society of Anesthesiologists (ASA) score having p-value 0.045, hospital stay with p<0.001 and surgical type and previous surgical history with p<0.001, were as duration of surgery was having <0.001.CONCLUSION: Prevention of SSI’s requires a multipronged approach with emphasis on optimizing preoperative issues, adhering to strict protocols during the intraoperative period and addressing and optimizing metabolic and nutritional status in post-operative period.